Coincidence of increasingly volatile winters in China with Arctic sea-ice loss during 1980–2018 - Yang Chen; Zhen Liao; Panmao Zhai (Environmental Research Letters, 2019)
Despite intense discussions on the recent boom of mid-latitude wintertime cold extremes, co-variations of warm and cold extremes, i.e. winter temperature volatility, has garnered substantially less attention. Apart from using temperature extremes’ frequency and intensity, we also define ‘temperature whiplash’, which depicts rapid switches between warm and cold extremes, to measure winter temperature volatility in China. Results show that Northeast-, Northwest-, Southwest-, Southeast-China and the Yangtze River Valley have experienced increasingly volatile winters after 1980, co-occurring with precipitous decline in Arctic sea-ice. This enhanced volatility has a strong expression in significant increases in temperature whiplash events, with some hotspots also seeing both warm and cold extremes become more frequent and/or intense. An observation-based detection analysis highlights the dominance of intrinsic atmospheric variability over both anthropogenic warming and sea-ice decline during 1980–2018 in driving winters in China to be more volatile over this period.